Disagree and you shall be valued: a semiotic examination of how photojournalism constructs "valuable" Iranian bodies across Time. Issue 1 (1st January 2023) - Durrani, Sameera
ABSTRACT: Departing from the synchronic trend dominant in social semiotics research, this study examines the diachronic interplay between semiotic cues governing power relations, and global political power dynamics. It examines thirty years of photographic coverage given to Iran in Time Magazine, focusing specifically on diachronic interaction analysis (Kress and van Leeuwen 2006, Reading Images: The Grammar of Visual Design. London: Routledge). The significance of these discourses is examined with an interdisciplinary conceptual lens comprising of social semiotics (Kress and van Leeuwen 2006, Reading Images: The Grammar of Visual Design. London: Routledge) and critical theory (Butler 1993, Bodies That Matter: On the Discursive Limits of Sex. New York: Routledge). The analysis reveals the even amongst a routinely "othered" national community, some actors are rendered more "valuable" by the camera. Specifically, the interactive cues of gaze, camera angle and social distance accord more power to male dissidents, and female trailblazers, discursive choices serving as an indictment of Iran's socio-political systems. Furthermore, this paper extends van Leeuwen's (2008, "Representing Social Actors." In Discourse and Practice, edited by T. van Leeuwen. New York: Routledge) work on visual "othering, " and suggests three new categories for examining how visual cues create "valuable bodies": adjacency, subjectivation, and empowerment.